2016
DOI: 10.3389/fmars.2016.00053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feed Species and HUFA Composition on Survival and Growth of the Longsnout Seahorse (Hippocampus reidi)

Abstract: Globally, wild seahorse populations are threatened due to, habitat destruction and unsustainable human exploitation among others. Furthermore, aquaculture-based mass-scale rearing is still uncommon due to the low survival rates of seahorse juveniles and exceptionally high feed costs. Previous studies have demonstrated the importance of both highly unsaturated fatty acid (HUFA) supplies and a copepod-based rearing for seahorse survival and growth. As the latter is expensive, the question arises as to how high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Food species influence on the growth rate and survival of newborn H. reidi were reported in several previous studies (Olivotto et al., 2008; Schubert, Vogt, Eder, Hauffe, & Wilke, 2018). Schubert et al (2018) reported that H. reidi larvae fed either diets of Selco S. presso‐enriched Artemia nauplii and a mixed diet of Artemia and copepod ( Eurytemora affinis ) had good survival, but the diet mixture resulted in superior weight and height growth. Different effects of food species and feeding stratagems on H. reidi growth and survival was also found by Olivotto et al.…”
Section: Discussionsupporting
confidence: 58%
“…Food species influence on the growth rate and survival of newborn H. reidi were reported in several previous studies (Olivotto et al., 2008; Schubert, Vogt, Eder, Hauffe, & Wilke, 2018). Schubert et al (2018) reported that H. reidi larvae fed either diets of Selco S. presso‐enriched Artemia nauplii and a mixed diet of Artemia and copepod ( Eurytemora affinis ) had good survival, but the diet mixture resulted in superior weight and height growth. Different effects of food species and feeding stratagems on H. reidi growth and survival was also found by Olivotto et al.…”
Section: Discussionsupporting
confidence: 58%
“…In recent years, studies have focused on the use of wild zooplankton or cultured copepods to improve survival and growth during the larviculture of H. reidi (Hora & Jouyex, ; Olivotto et al, ; Randazzo et al, ; Schubert, Vogt, Eder, Hauffe, & Wilke, ; Souza‐Santos et al, ; Willadino et al, ). Despite the benefits of these types of live food, they present a number of disadvantages such as risk of contamination with pathogens (Conceição, Yúfera, Makridis, Morais, & Dinis, ; Su, Cheng, Chen, & Su, ), variable composition (Hoff, Snell, & Neslen, ) and seasonality (Knuckey, Semmens, Mayer, & Rimmer, ), as in the case of wild zooplankton difficulties in mass production, high cost and intensive work for copepod cultivation (Knuckey et al, ; Vu, Jepsen, & Hansen, ).…”
Section: Introductionmentioning
confidence: 99%
“…The results achieved on biological indicators such as growth and mortality as well as on the contribution of growth and metabolism to tissue turnover demonstrate that extending the feeding on copepods from 6 DAR to 11 DAR enhanced the overall condition and welfare of H. reidi juveniles. Due to the high cost of copepod production, a co-feeding regime including copepods-Artemia has been proposed for large-scale ex-situ production [65].…”
Section: Discussionmentioning
confidence: 99%